The Rulings of the Israeli Military Courts and International Law. (14th August 2019) - Ramati, Nery
Abstract: International humanitarian law (IHL) provides the occupying power extensive legal tools in order to allow it to control and govern the local occupied population, with the possibility of establishing a military law system being one of the most influential. The military law system gives the Military Commander of the occupied area an immense power as a potential legislator and judicial authority, but what happens when this legal system encounters the limitations placed by IHL in general and Occupation Law in particular? To examine this question, this article will present the case of the Israeli Military Court system in the Palestinian Occupied Territories and its use, abuse and misuse of international law norms. Based on the 5565 published rulings of the Military Court of Appeals, this research identifies all of the cases that refer to international law. This article suggests that the evolving approaches of the courts to international law are, in fact, a tool to justify and advance Israeli interests over the rights of the Palestinian defendants. Moreover, the article presents the potential impact these rulings have on the law in Palestine, the law in Israel and customary international law.